Basic Income in the World Arguments, Experiments, History - Marek, Hrubec (Epocha, 2022)
This book offers an introduction to the important idea and practice of unconditional basic income, which is becoming a topic increasingly discussed not only among researchers but also among citizens and the politicians who represent them. The topic is also increasingly making its way into the mass media. Unconditional basic income is a financial sum that is provided to all citizens (or otherwise legally defined residents) by the state (or a city, a county etc.) at regular intervals (usually monthly) without any conditions being attached, i.e. regardless of whether the citizen has other income from wages or other sources, regardless of age, sex and gender, marital status or other characteristics. The provision of a basic income enables citizens' basic needs to be met and their creative potential to be unlocked for their other activities which could then significantly raise their standard of living. This book discusses basic income by presenting the main arguments and experiments with basic income in Europe, the Americas, Africa, and Asia. Basic income offers the possibility of a major social and civilizational change for all.
Keywords: Sociologie